Two-Dimensional van der Waals Material PdPSe: Investigation on Electrical Transport - Cho, Sooheon; Jeong, Byung Joo; Choi, Kyung Hwan; Lee, Bom; Jeon, Jiho; Lee, Sang Hoon; Kim, Bum Jun; Lee, Jae Hyun; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (ACS Applied Electronic Materials, 2023)
The unique puckered pentagonal structure of the layered semiconductor material palladium phosphorus selenide (PdPSe) has gathered attention, but its electronic performance has not been thoroughly investigated. In this study, PdPSe is synthesized via chemical vapor transport, and its thickness-dependent electrical properties are examined from 1.4 to 309 nm via the field-effect transistor (FET) measurement. The material exhibits n-type semiconducting behavior, with relatively high mobility observed at a specific thickness range, reaching up to 4.9 cm2 V-1 s-1 with a maximum on/off ratio of 2.86 × 108 at a Vds of 1 V. The transport mechanism is analyzed by calculating the Schottky barrier height (SBH) using a thermionic emission model. Temperature-dependent analysis revealed that the device has a minuscule SBH and the PdPSe FET device follows the Fowler-Nordheim tunneling model. Through drain-voltage-dependent FET characteristic analysis, an improvement in carrier mobility up to 33 cm2 V-1 s-1 is observed at a high drain voltage of 10 V. These findings provide fundamental insights into the performance of PdPSe FETs and their potential use in next-generation electronic applications based on two-dimensional (2D) materials.
Keywords: Charge transport mechanisms; Field-effect transistor; Palladium phosphorus selenide; Property; Schottky-barrier heights; Selenides; Thickness-dependent property; Two-dimensional; Two-dimensional materials; Van der Waal; charge transport mechanism; field-effect transistor; PdPSe; thickness-dependent property; two-dimensional material